Sexualidade e Cuidado na Pessoa Idosa. Atitudes e Perceções de Cuidadoras Informais. - Sara Catarina Campos Adão (2022)
The demographic ageing of the population has motivated the increase of scientific production in this area. Most studies have been demystifying beliefs and prejudices associated with the experience of this dimension during the ageing process. Given that the increase in average life expectancy is not inseparable from a higher prevalence of situations of dependence, studies are emerging within the scope of elderly care, especially at the institutional level. However, there is still a need for research focused on people who provide informal care to dependent older people, namely in terms of their experiences of sexuality. Thus, this research aimed to analyse the attitudes and reactions of the informal caregivers of older people, looking at the expression and experience of the sexuality of the people under their care, their preparation and the adversities experienced when addressing issues of this dimension, and, finally, their perceptions about the necessary and existing support for the provision of informal care that meets the needs of dependent older people and caregivers in an integrated and healthy way. Therefore, semi-structured interviews were conducted with 7 informal caregivers of older people, aged between 38 and 74 years old. The analysis of the participants' accounts was performed through thematic analysis (Braun & Clarke, 2006), which led to the identification of a central organizer that we named "dictatorship" of being a (good) caregiver, around which two main themes are developed: The caring role and Attitudes and perceptions about sexuality of people in care. The main conclusions of this research highlight the training needs of caregivers, in order to provide theoretical and technical knowledge regarding the provision of specific care to dependent people, as well as skills to respond to the needs of older people in terms of the expression and experience of sexuality. The study of the perspectives of informal caregivers of older people is considered imperative, with a view to planning and structuring public policies and programmes of social support to the family, oriented to the reality of caregivers and older people, ensuring their empowerment and the provision of care more suited to particular needs.